2010
DOI: 10.1080/1522886x.2010.496109
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Seed Rate to Suppress Weeds and to Increase Yield in Aerobic Direct-seeded Rice in Northwestern Indo-Gangetic Plains

Abstract: Weed infestation is a major constraint to widespread adoption of aerobic, direct-seeded rice (Oryza sativa L.). Higher than optimum initial seeding density for obtaining more panicles/m 2 is often accompanied by reduced panicle size and 1,000-grain weight, and high rate of spikelet sterility. On the other hand, weeds in plots with a lower seeding rate have a better chance to emerge, grow and build up a strong population and thus pose a serious crop-weed competition. Experiments were conducted during kharif (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
4
16
0
Order By: Relevance
“…Similar results were also observed by many researchers (Phuong et al 2005;Anwar et al 2011). Mahajan et al (2010) opined that closer spacing can keep the weed flora under check through smothering effect. Guillermo et al (2009), on the other hand, revealed that higher plant densities might have a competitive advantage over weeds due to fast canopy development resulted in reduced weed growth.…”
Section: Weed Density and Dry Weightsupporting
confidence: 78%
“…Similar results were also observed by many researchers (Phuong et al 2005;Anwar et al 2011). Mahajan et al (2010) opined that closer spacing can keep the weed flora under check through smothering effect. Guillermo et al (2009), on the other hand, revealed that higher plant densities might have a competitive advantage over weeds due to fast canopy development resulted in reduced weed growth.…”
Section: Weed Density and Dry Weightsupporting
confidence: 78%
“…The choices of genotypes and seeding rates are crucial yield determinants in DSR. Seed rates in DSR influence crop growth and grain yield (Mahajan et al, 2010). The genetic potential of genotypes can be used by selecting an optimum seed rate.…”
mentioning
confidence: 99%
“…In countries such as Vietnam, 150-200-kg ha −1 seeding rates are being used, while in northwest India, farmers use a rate of 15-25 kg ha −1 [48]. Farmers use high seeding rates to compensate for poor quality seeds and to cover the risk of rodent, bird, insect, and nematode attacks [12].…”
Section: Tillage Systems and Land Preparationmentioning
confidence: 99%